(untitled) (Samarra Journal of Pure and Applied Science, 2026)
Candida is a natural microscopic organism are yeasts that are found in the normal microorganisms of the oral cavity, opportunistic that cause diseases when conditions are created, overgrowth of yeasts leads to tissue invasion and causes diseases. One of the diseases caused by yeast overgrowth in children is oral thrush, this study was conducted at the Women’s and Children’s Hospital in Ramadi, where 100 oral swabs were collected from infants with oral thrush aged 1 month-2 years and then morphological and biochemical tests were conducted on positive growth isolates. The results showed that 77 isolates were positive growth by 77% and 23 isolates by 23% showed no growth. Four types of Candida were identified, Candida albicans with 49.35%, followed by Candida krusei with 28.57%, Candida tropicalis with 14.28% and Candida glabrata with 7.79%. The results also showed a statistically significant difference between the infection and the age group, where the most infected age group between 1 month-1 year by 74.36%, and the results also showed that the cases of oral fungal infection in infants are associated with artificial feeding by 90.91%.